A Brief Review on Frequency Encoding: Developing an All Optical Latch Logic Using Frequency Encoding (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In case of super-fast optical computation and communication, frequency encoding techniques are found to be very promising and reliable one. Optical logic gates based on the principle of frequency conversion of some non-linear materials play the key role for the implementation of a frequency encoded data processing system. Again semiconductor optical amplifier has already been established successfully for frequency conversion. In frequency encoding system, different frequencies of light signal are used for representation of binary bits 0 or 1 instead of intensity variation. For example 0 and 1 bits of Boolean logic can be coded by two different frequencies of light signa and respectively. In this communication, we propose the method of developing an optical memory or a NOT based latch. Several types of phase encoded, polarization encoded and intensity encoded optical memories have been reported earlier, including latch also, whereas this proposal have been planned to develop an all optical latch logic using frequency encoded principle and it offers a reliable and faithful processing rather than other established techniques.